Morphogenesis of the Infectious HIV-1 Virion - Sakuragi, Jun-Ichi (Frontiers in Microbiology, 2011)
The virion of HIV-1 is spherical and viral glycoprotein spikes (gp120, gp41) protrude from its envelope. The characteristic cone-shaped core exists within the virion, caging the ribonucleoprotein (RNP) complex, which is comprised of viral RNA, nucleocapsid (NC) and viral enzymes. The HIV-1 virion is budded and released from the infected cell as an immature donut-shaped particle. During or immediately after release, viral protease (PR) is activated and subsequently processes the viral structural protein Gag. Through this maturation process, virions acquire infectivity, but its mechanism and transition of morphology largely remain unclear. Recent technological advances in experimental devices and techniques have made it possible to closely dissect the viral production site on the cell, the exterior – or even the interior – of an individual virion, and many new aspects on virion morphology and maturation. In this manuscript, I review the morphogenesis of HIV-1 virions. I focus on several studies, including some of our recent findings, which examined virion formation and/or maturation processes. The story of novel compound, which inhibits virion maturation, and the importance of maturation research are also discussed.